Implementation of the Merkle-Hellman knapsack cryptosystem into station-to-station protocol / Nurzhulaika Yahya, Noor Izzah Agil and Nur ‘Afini Nordin - Yahya, Nurzhulaika; Agil, Noor Izzah; Nordin, Nur ‘Afini (2023)
The Merkle-Hellman Knapsack Encryption Cryptosystem is the first widely used public key encryption algorithm. Martin Hellman and Ralph Merkle came up with the idea in 1978. The station-to-station protocol is integrated with the Merkle-Hellman knapsack cryptosystem for a particular use or application when the Merkle-Hellman knapsack cryptosystem is included into the protocol. A cryptographic mechanism called station-to-station is used to provide a secure channel of communication between two parties. Mutual authentication and key exchange for cryptography are involved. Using the Merkle-Hellman knapsack cryptosystem as a part of the station-to-station protocol to improve the protocol's security or effectiveness might be considered integrating the Merkle-Hellman knapsack cryptosystem. The objectives of this study are to modify Merkle-Hellman knapsack cryptosystem to be a digital signature. Then, to implement Merkle-Hellman digital signature into Station-To-Station Protocol. Next, to develop maple for interface the proposed method. Finally, to compare the strength of the security level of the proposed method with the other digital signature. This study aims to demonstrate the implementation of the Merkle-Hellman cryptosystem into the Station-to-Station protocol as a new enhancement. This study also develops maplet to show the process of protocol and supported by manual calculation. In conclusion, Station-to-Station securely exchanges keys using Merkle-Hellman knapsack cryptosystem. Despite challenges, the study achieved objectives and validated the system through manual calculations. Comparing articles highlighted super increasing importance for security. However, errors in sequence creation can compromise it. Modern protocols prefer alternatives like Diffie-Hellman or elliptic curve cryptography. Recommendations for future improvements in the Station-to-Station protocol include implementing a signcryption scheme, combining digital signature and encryption functionalities for enhanced security and cost-efficiency. This approach reduces the operational cost for signature generation and verification. Overall, objectives were successfully met.